A novel design of window function modulated meander-line-coils EMATs for unidirectional Rayleigh waves generation and sidelobes suppression. (October 2021) - Xie, Yuedong; Li, Jiyao; Huang, Pu; Zhang, Le; Tian, Wenbin; Lu, Mingyang; Zhao, Xin; Huo, Zhilin; Liu, Zenghua; Wang, Shupei; Huang, Ruochen; Yin, Wuliang; et al.
Abstract: A new design of Window Function modulated electromagnetic acoustic transducers (EMATs) to generate unidirectional Rayleigh waves is proposed. The novel EMATs, Rectangular-Window-Meander-Line-Coil EMATs (RWMLC-EMATs) and Kaiser-Window-Meander-Line-Coil EMATs (KWMLC-EMATs), contain two variable length meander line coils with a spacing of one quarter of Rayleigh waves' wavelength; the excitation signals for these two coils have a phase difference of 90 0 . The structure of the variable wire length determines the level of the sidelobes suppression; the structure of two meander line coils combined with the excitation signals with a phase difference of 90 0 determine that Rayleigh waves only propagate along one direction. RWMLC-EMATs and KWMLC-EMATs are analyzed via a wholly analytical method and are validated with experiments, which proves the feasibility of the proposed EMATs structure. In addition, the effect of the wire step and the longest wire length are investigated analytically and experimentally. Results indicate that, wire step mainly affects the suppressed level of sidelobes – a large wire step leads to a small suppressed level of sidelobes. This work can be used for Rayleigh waves EMATs design and optimization to improve their defect detection capability.